Effect of Solvents on De-Cross-Linking of Cross-Linked Polyethylene under Subcritical and Supercritical Conditions - Lee, Hong-shik; Jeong, Ju Hyeong; Hong, Giyoung; Cho, Hang-Kyu; Baek, Bum Ki; Koo, Chong Min; Hong, Soon Man; Kim, Jaehoon; Lee, Youn-Woo (AMER CHEMICAL SOC, 2013)
The effect of various solvents on the de-cross-linking reaction of cross-linked polyethylene under subcritical and supercritical conditions was studied. The gel content of the de-cross-linked polyethylene decreased from 60 to 0.8-2.5% at 380 degrees C within 5 min in all of the solvents tested in this study. When water, ethanol, and 2-propanol were used, the M-w of the decross-linked polyethylenes decreased from 349,000 to 200,000-227,000 g/mol, and much lower M-w values of 70,000-90,000 g/mol were observed when acetone and diisopropyl ether were used. The de-cross-linked polyethylenes treated in the different solvents had a very similar chemical structure to raw polyethylene. According to a kinetic study using a first-order reaction model, the de-cross-linking rate in each solvent increased in the order 2-propanol < ethanol < n-hexane < water < methanol << diisopropyl ether << acetone at 350 degrees C.
Keywords: DECOMPOSITION; DEPOLYMERIZATION; TEREPHTHALATE; METHANOL; FLUIDS; WATER; RESIN